THE ROLE OF THE COMBINED USE OF FOAM HYSTEROSALPINGOSONOGRAPHY AND DIAGNOSTIC LAPAROSCOPY IN CHOOSING TREATMENT TACTICS IN PATIENTS WITH IDIOPATHIC INFERTILITY - Nigora A. Mamasalieva; Mukhayokhon T. Khamdamova; Shokhista A. Mamasolieva (Central Asian Journal of Medicine, 2025)
Background. The mutually exclusive use of such diagnostic methods like HyFoSy and DL has long been established in patients with idiopathic infertility. However, more and more reproductive specialists have recently been inclined to use them together in order to improve outcomes of IUI. Objectives. investigate the combined practical application of HyFoSy and DL to improve IUI outcomes in patients with II and ONMT. Materials and methods. retrospective study was conducted at the Department of Reproductive Medicine, AIMS Medical Clinic, Addu, Maldives. 47 women with idiopathic infertility referred for intrauterine insemination between 2021 and 2024 and 48 women with unilateral fallopian tube occlusion who underwent DL and HyFoSy were analyzed. Conclusions. the tendencies revealed by us indicate a possible benefit of combined performance of HyFoSy and DL in patients suffering from II and ONMT, which requires further research in this direction.